THE HISTORICAL PAST AND ENVIRONMENTAL SIGNIFICANCE OF KASHKADARYA OASIS - Karimov Bahrom Djalolovich; Rakhmonov Malik (Sciental Journals Publishing, 2025)
In this article are carried out on the problems of natural resources and their oasis, history, ecology, storage and restoration. Measures are analyzed. The Kashkadarya oasis is distinguished by its natural resources and historical heritage as an ecological and economically important territory of Central Asia. The article also pays special attention to ensuring environmental sustainability, effective management of natural resources and solutions to vital problems.
Keywords: Ecological conditions, natural resources, sources of water, Kashkadarya Biodiversity, ecology, oasis.